Primary Total Knee Arthroplasty - Rozim Zorzi, Alessandro; Batista de Miranda, João (IntechOpen, 2018)
This book presents a compilation of topics related to primary total knee arthroplasty. The chapters cover, in a clear and didactic way, the current themes, written by experts from the area, from different parts of the world. Topics related to the three surgical phases (before surgery, during surgery, and after surgery) are discussed here. This is very important because the surgeon is not a "factory worker." First of all, it is a medicine doctor who has to feel and understand the particularities of each patient. Demographic studies show an aging population. Osteoarthritis and inflammatory diseases are becoming much more prevalent. In addition, a worldwide epidemic of trauma has led to the need for arthroplasties much more frequently. Therefore, total knee arthroplasty will be an increasingly important subject.